Socially necessary superfluity: Adorno and Marx on the crises of labor and the individual. (September 2019) - Arzuaga, Fabian
This article considers Theodor W. Adorno's thesis of the 'liquidation of the individual' as a contribution to the critique of political economy insofar as it links structural economic imperatives of the capitalist order to transformations of consciousness and human conduct. For Adorno, such 'liquidation' amounts to not only the superfluity of bourgeois individuality as an anthropological type but also to the objective superfluity of actually living individuals. I develop Adorno's argument that the 'form and organization of labor' in capitalism produces these forms of superfluity by turning to Marx's critique of value with an emphasis on the logic of 'socially necessary labor-time.' My argument is that as long as society is enthralled to the ongoing self-valorization of value (i.e. capital), social reproduction makes 'socially necessary' the superfluity of individuality as well as actually-living human individuals. In short, the anthropological decomposition of the bourgeois individual and the generation of 'surplus populations' are expressions of the same contradiction: the necessity and superfluity of labor in capitalism. After illustrating some current expressions of this contradiction evident in the global 'crisis of work' – including the displacement and transformation of labor by automation and the massive growth of the 'global slums' – I suggest that further analysis of the temporal contradictions of the law of value evinces the conditions of an emancipated individual in a post-work society.